Gamma‐aminobutyric acid edited echo‐planar spectroscopic imaging (EPSI) with MEGA‐sLASER at 7T. Issue 2 (29th August 2018) - Magnusson, Peter O.; Boer, Vincent O.; Marsman, Anouk; Paulson, Olaf B.; Hanson, Lars G.; Petersen, Esben T.
Abstract : Purpose: For rapid spatial mapping of gamma‐aminobutyric acid (GABA) at the increased sensitivity and spectral separation for ultra‐high magnetic field strength (7 tesla [T]), an accelerated edited magnetic resonance spectroscopic imaging technique was developed and optimized for the human brain at 7 T. Methods: A MEGA‐sLASER sequence was used for GABA editing and volume selection to maximize editing efficiency and minimize chemical shift displacement errors. To accommodate the high bandwidth requirements at 7 T, a single‐shot echo planar readout was used for rapid simultaneous encoding of the temporal dimension and 1 spatial. B 0 and B 1 field aspects specific for 7 T were studied together with correction procedures, and feasibility of the EPSI MEGA‐sLASER technique was tested in vivo in 5 healthy subjects. Results: Localized edited spectra could be measured in all subjects giving spatial GABA signal distributions over a central brain region, having 45‐ to 50‐Hz spatial intervoxel B 0 field variations and up to 30% B 1 field deviations. MEGA editing was found unaffected by the B 0 inhomogeneities for the optimized sequence. The correction procedures reduced effects of intervoxel B0 inhomogeneities, corrected for spatial editing efficiency variations, and compensated for GABA resonance phase and frequency shifts from subtle motion and acquisition instabilities. The optimized oscillating echo‐planar gradient scheme permitted full spectral acquisition at 7 T and exhibited minimal spectral‐spatial ghosting effects for the selected brain region. Conclusion: The EPSI MEGA‐sLASER technique was shown to provide time‐efficient mapping of regional variations in cerebral GABA in a central volume of interest with spatial B 1 and B 0 field variations typical for 7 T.